2011
DOI: 10.1002/jmv.23192
|View full text |Cite
|
Sign up to set email alerts
|

Detection of herpes simplex virus (1 and 2), varicella‐zoster virus, cytomegalovirus, human herpesvirus 6 and enterovirus in immunocompetent tunisian patients with acute neuromeningeal disorder

Abstract: Enteroviruses (EVs) and human herpesviruses (HHVs) are involved frequently in acute neurological disorders of viral etiology. This study aimed to investigate the incidence of herpes simplex virus types-1 (HSV-1) and 2 (HSV-2), varicella-zoster virus (VZV), cytomegalovirus (CMV), human herpesvirus 6 (HHV-6) and human enteroviruses (EVs) in cerebrospinal fluid (CSF) samples of Tunisian immunocompetent patients with neuromeningeal disorders. The patients had been hospitalized at the Fattouma Bourguiba University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 54 publications
5
8
0
Order By: Relevance
“…The present results, showing that viral etiology could be identified by PCR in more than 50% of patients with aseptic meningitis, were consistent with previous findings [Nowak et al, ; Kupila et al, ; Nahdi et al, ; de Ory et al, ]. Our results showed that EV was the most frequent cause of aseptic meningitis followed by VZV.…”
Section: Discussionsupporting
confidence: 93%
“…The present results, showing that viral etiology could be identified by PCR in more than 50% of patients with aseptic meningitis, were consistent with previous findings [Nowak et al, ; Kupila et al, ; Nahdi et al, ; de Ory et al, ]. Our results showed that EV was the most frequent cause of aseptic meningitis followed by VZV.…”
Section: Discussionsupporting
confidence: 93%
“…In our cohort, EV was the most common cause of meningitis, which is consistent with recent studies from northern and southern Europe , North America , North Africa and South Korea . Interestingly, EV infection seems to be more prevalent in southern Europe compared to central or northern Europe (Tables S2–S5).…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, here symptoms such as nausea and vomiting were more often observed corresponding to an assumed portal of entry of EV in the gastrointestinal region. It was found that inflammatory signs in CSF are rather low, which is consistent with the findings of other studies [2,11]. The latency between onset of symptoms and admission to hospital was shorter than in any other virus group suggesting that EV meningitis has a more rapid onset a more rapid onset.…”
Section: Discussionsupporting
confidence: 90%
“…However, it has also been demonstrated that detection of CMV DNA in CSF samples were not necessarily correlated with a latent CMV infection [Studahl et al, 1995]. CMV was detected in 5 CSF samples of immunocompetent patients, a result similar to that observed by two studies [Mendoza et al, 2007;Nahdi et al, 2012]. These findings also underline an important role of CMV in acute CNS infection in immunocompetent individuals.…”
Section: Discussionsupporting
confidence: 74%